Understanding the Links between Charismatic Leadership, Intrinsic Motivation and Tacit Knowledge Sharing among MSME Employees - Novitasari, Dewiana; Haque, Marissa GraceHaque; Supriatna, Heri; Asbari, Masduki; Purwanto, Agus (International Journal of Social and Management Studies, 2021)
This study aims to examine the effect of charismatic leadership on intrinsic motivation and tacit knowledge sharing. This study also investigates the central role of intrinsic motivation as a mediating variable between charismatic leadership and tacit knowledge sharing. This study adopted a simple random sampling method with 61 samples of employees from five MSME companies in Banten. With the help of SmartPLS 3.0 software, the results of this study indicate that charismatic leadership has a significant direct effect on intrinsic motivation but does not directly affect tacit knowledge sharing. However, this study found the fact that charismatic leadership has a significant indirect effect on tacit knowledge sharing through the mediation of intrinsic motivation. So, intrinsic motivation acts as a full mediator in this research model